Microbiological analysis and determination of antibacterial activity of apple samples collected from local markets in Dhaka city, Bangladesh (Stamford Journal of Microbiology, 2017)
Present study attempted to detect the prevalence of contaminating microorganisms in 10 categories of local market apple samples commonly consumed in Dhaka city, Bangladesh. A significant number of total viable bacteria were quantified up to 106 cfu/g in these samples. Staphylococcus spp. was the predominant isolate within a range of 1.0×104 3.2×106cfu/g whereas Escherichia coli, Klebsiella spp., Salmonella spp., Shigella spp., Pseudomonas spp. and Vibrio spp. were also quantified. Fungal contamination (within the range of 105 cfu/g 107cfu/g) was also observed. Alarmingly most of the bacterial isolates present in the samples were proved to be multi-drug resistant. Antibacterial activity of the samples was tested against some common bacterial isolates but was found to be ineffective.Stamford Journal of Microbiology, Vol.6(1) 2016: 11-15